Redox and melting characteristics of Mn-based ores for high-temperature thermochemical energy storage - Liu, Lei; Xu, Wenting; Liu, Hanzi (Frontiers in Energy Research, 2024)
Redox and melting characteristics of Mn-based ores were investigated to test their potential use in thermochemical energy storage (TCES). Two Mn-based materials (FJ and LY) were natural ores with the Mn content higher than 35 wt%, and one Mn-based material was prepared by adding an MgO–kaolin inert support into LY ores to increase its melting temperature. Cyclic reduction and oxidation reactivity of these Mn-based materials was studied via thermogravimetric analysis (TGA), and the melting behaviors of these materials were investigated by using a melting test setup with an optical camera–image system. It was found that the oxygen capacity of the FJ Mn ore can approach ∼1.50 wt%, while the LY Mn ore had only 0.42 wt%–0.69 wt% oxygen capacity The deformation temperature of the FJ Mn ore is higher than that of the LY Mn ore, and the melting temperatures of the LY Mn ore can be significantly improved with the addition of an MgO–kaolin inert support, while the reactivity is decreased due to the addition of the MgO–kaolin inert material. This study proves that manganese ores with high oxygen capacity and deformation temperature have potential as TCES materials. For some manganese ores with low deformation temperatures, it is necessary to improve their melting temperatures and ensure oxygen capacity for high-temperature TCES applications.